Three-dimensional analysis of acetabular orientation using a semi-automated algorithm. Issue 1 (1st January 2019) - Lee, Changhwan; Jang, Jongseong; Kim, Hyung Wook; Kim, Young Soo; Kim, Yeesuk
Abstract: Understanding the morphology of the acetabulum is necessary for preoperative evaluation in hip surgery. The purpose of this study was to (1) establish a novel method for measuring three-dimensional (3D) acetabular orientation, (2) quantify the reliability of this method, and (3) describe relevant characteristics of three-dimensional (3D) acetabular orientation among normal Asian subjects. Computed tomography (CT) scans of the pelvis that had been performed for suspected non-musculoskeletal conditions were obtained from 200 subjects (60 males, 140 females). A novel method was developed to measure 3D acetabular orientation with a semi-automatically determined pelvic coordinate system based on the anterior pelvic plane (APP). To quantify the robustness of our method, we analyzed the results obtained from 20 patients at different times and with different raters and pelvic poses in the same CT volume. To determine morphological differences of the acetabulum by age and sex, we analyzed the parameters of 200 CT volumes. Each intraclass correlation coefficient (ICC) values for intra- and inter-observer reliability were over 0.975 and 0.945, demonstrating high reliability. Furthermore, agreement between the angles determined from the original volume and the rotated volume was nearly perfect (ICCs > 0.956). Multiple linear regression analysis with age and sex as covariates indicated that acetabular inclination was not significantly associated with age ( p = 0.687) or sex ( p = 0.09). There was also no evidence that acetabular anteversion was associated with age ( p = 0.383) or sex ( p = 0.53). Our method showed excellent reliability for determining acetabular orientation, as it is robust, fast, and easily applicable to larger populations. In addition, the results of the analysis of acetabular orientation by age and sex can be used as a reference in various diagnostic procedures in orthopedics.